Development of Portable Oxygen Concentrator Device for COVID-19 Patient - Hwai Ing, Soon; Jamin, Nur Fatihah; Karunaniti, Thilaka; Azman, Nurfatihah; Zhi Jian, Low; Mohammad, Nur Farahiyah; Mohd Nasir, Nashrul Fazli (Multidisciplinary Applied Research and Innovation, 2021)
Coronavirus disease (COVID-19) threatens to overwhelm our medical infrastructure at the global stage causing spikes in mortality rates because of the shortage of critical medical equipment such as ventilators. Most of the people infected with the SARS-CoV2-virus will experienced shortness of breath due to low levels of oxygen in the body known as hypoxia. This condition is referred to as "silent" or "happy hypoxia," when oxygen saturation is below 90% within the body, but the person can still normally breathe. Therefore, it is very vital to regularly monitor COVID-19’s patient oxygen saturation level in order to supply adequate oxygen needed through the oxygen concentrator of a portable oxygen compressor. Thus, the main objective of this project is to develop a portable oxygen concentrator device to help patient with low oxygen level particularly the COVID-19’s patient. The device was developed with pulse oximeter to measure the oxygen level (oxygen saturation) of the blood with curved cylindrical shape prototype body. The system powered by the rechargeable solar battery that supply direct current to the system. The ESP8266 Wemos NodeMCU was used as the main microcontroller while the GY-MAX30100 oximeter is used to monitor the SpO2 level and determine the user’s condition, the severity of silent hypoxia and to figure out the necessity of oxygen therapy. The result and suggestions will be displayed on an OLED screen together with a light indicator after the testing and tracking is done. In addition to that, if the user hypoxia is too severe, SpO2 level less than 86% is detected, buzzer will be alarmed, and light indicator will be lighted up asides from displaying and sending notifications to the user.